Whole exome sequencing in childhood-onset lupus frequently detects single gene etiologies - Irit Tirosh; Shiri Spielman; Ortal Barel; Reut Ram; Tali Stauber; Gideon Paret; Marina Rubinsthein; Itai M. Pessach; Maya Gerstein; Yair Anikster; Rachel Shukrun; Adi Dagan; et al. (BMC, 2019)
Abstract Background Systemic lupus erythematosus (SLE) comprise a diverse range of clinical manifestations. To date, more than 30 single gene causes of lupus/lupus like syndromes in humans have been identified. In the clinical setting, identifying the underlying molecular diagnosis is challenging due to phenotypic and genetic heterogeneity. Methods We employed whole exome sequencing (WES) in patients presenting with childhood-onset lupus with severe and/or atypical presentations to identify cases that are explained by a single-gene (monogenic) cause. Results From January 2015 to June 2018 15 new cases of childhood-onset SLE were diagnosed in Edmond and Lily Safra Children's Hospital. By WES we identified causative mutations in four subjects in five different genes: C1QC, SLC7A7, MAN2B1, PTEN and STAT1. No molecular diagnoses were established on clinical grounds prior to genetic testing. Conclusions We identified a significant fraction of monogenic SLE etiologies using WES and confirm the genetic locus heterogeneity in childhood-onset lupus. These results highlight the importance of establishing a genetic diagnosis for children with severe or atypical lupus by providing accurate and early etiology-based diagnoses and improving subsequent clinical management.